Managing Disputes for a Sustainable Construction: A Perspective of Settlement Facilitating Elements in Negotiations - Lin, S.; Li, Keyao (Eden); Cheung, S. (2023)
Construction 4.0 presents a multitude of opportunities; however, it also increases the chance of disputes. Efficient dispute management contributes to the sustainable production of construction works. Enhancing negotiation management and negotiators’ settlement ability is valuable, given that negotiation is recognized as the most effective dispute resolution method. This study explores negotiation settlement by identifying negotiators’ settlement facilitating elements in construction dispute negotiation (CDN). A purposive literature review identified six key elements, naming preparation, integration, goodwill, continuity, commitment, and self-efficacy. With data collected from experienced construction dispute negotiators, the partial least squares structural equation modeling (PLS-SEM) results confirmed the significance of these elements. Accordingly, recommendations for negotiators include (i) technique (i.e., good preparation and applying integrative tactics); (ii) interaction (i.e., showing goodwill and relationship maintenance); and (iii) attitude (i.e., commitment to negotiate and being confident) if the negotiation settlement is desired. Management can implement these recommendations in their training manual to cultivate negotiators’ problem solving and settlement-oriented mindset. Negotiators can also review their behaviors throughout the negotiations and make timely adjustments as deemed necessary. Reaching an amicable negotiated settlement would not only save resources, preserving business relationships is of equal importance for a sustainable construction industry.